Analisis perbandingan rencana strategis tahun 2022 pada perbankan syariah di Indonesia - Imro’ah, Wulidatul; Rokhmah, Miftakhul; Laili, Silvia Nur (Maliki Interdisciplinary Journal, 2023)
Strategic Plans are very important to provide long-term guidance to bank management and employees in achieving the company’s vision and mission, as well as identifying strategies that will be used to achieve goals. This research aims to find out the comparison of the 2022 Strategic Plans at Bank Muamalat Indonesia (BMI), Bank Central Asia Syariah (BCAS), and Bank Syariah Indonesia (BSI). This type of research is a qualitative approach with descriptive methodology, utilizing data collection techniques such as interviews, observation and text analysis which are considered capable of explaining in detail, clearly and specifically. Based on the results of the analysis that has been carried out, the results obtained are that Bank Muamalat Indonesia (BMI), Bank Central Asia Syariah (BCAS), and Bank Syariah Indonesia (BSI) have the same strategic planning indicators, but the focus in their strategic planning is different. This research provides an understanding of the comparison of the 2022 Strategic Plan between Bank Muamalat Indonesia (BMI), Bank Central Asia Syariah (BCAS), and Bank Syariah Indonesia (BSI). Strategic Plans are very important to provide long-term guidance to bank management and employees in achieving the company’s vision and mission, as well as identifying strategies that will be used to achieve goals. This research aims to find out the comparison of the 2022 Strategic Plans at Bank Muamalat Indonesia (BMI), Bank Central Asia Syariah (BCAS), and Bank Syariah Indonesia (BSI). This type of research is a qualitative approach with descriptive methodology, utilizing data collection techniques such as interviews, observation and text analysis which are considered capable of explaining in detail, clearly and specifically. Based on the results of the analysis that has been carried out, the results obtained are that Bank Muamalat Indonesia (BMI), Bank Central Asia Syariah (BCAS), and Bank Syariah Indonesia (BSI) have the same strategic planning indicators, but the focus in their strategic planning is different. This research provides an understanding of the comparison of the 2022 Strategic Plan between Bank Muamalat Indonesia (BMI), Bank Central Asia Syariah (BCAS), and Bank Syariah Indonesia (BSI).